Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Standard view
Full view
of .
0 of .
Results for:
P. 1
Mathematical Methods for Physicists Webber/Arfken Selected Solutions from ch. 6

# Mathematical Methods for Physicists Webber/Arfken Selected Solutions from ch. 6

Ratings: (0)|Views: 3,790 |Likes:
Ch. 6: 6.1.3, 6.1.7, 6.2.5, 6.2.6, 6.3.3, 6.4.3, 6.4.4
Ch. 6: 6.1.3, 6.1.7, 6.2.5, 6.2.6, 6.3.3, 6.4.3, 6.4.4

### Availability:

See more
See less

06/26/2013

pdf

text

original

Physics 451 Fall 2004Homework Assignment #9 — Solutions
Textbook problems: Ch. 6: 6.1.3, 6.1.7, 6.2.5, 6.2.6, 6.3.3, 6.4.3, 6.4.4Chapter 66.1.3 Prove algebraically that
|
z
1
||
z
2
||
z
1
+
z
2
||
z
1
|
+
|
z
2
|
Interpret this result in terms of vectors. Prove that
|
z
1
|
<
|

z
2
1
|
<
|
z
+ 1
|
,
for
(
z
)
>
0We start by evaluating
|
z
1
+
z
2
|
2
|
z
1
+
z
2
|
2
= (
z
1
+
z
2
)(
z
1
+
z
2
) =
|
z
1
|
2
+
|
z
2
|
2
+
z
1
z
2
+
z
1
z
2
=
|
z
1
|
2
+
|
z
2
|
2
+ (
z
1
z
2
) + (
z
1
z
2
)
=
|
z
1
|
2
+
|
z
2
|
2
+ 2
(
z
1
z
2
)(1)We now put a bound on the real part of
z
1
z
2
. First note that, for any complexquantity
ζ
, we have
|
ζ
|
2
= (
ζ
)
2
+ (
ζ
)
2
(
ζ
)
2
. Taking a square root gives
|
ζ
| ≥ |
ζ
|
or
−|
ζ
|
ζ
|
ζ
|
. For the present case (where
ζ
=
z
1
z
2
) this gives
−|
z
1
||
z
2
|
(
z
1
z
2
)
|
z
1
||
z
2
|
. Using this inequality in (1), we obtain
|
z
1
|
2
+
|
z
2
|
2
2
|
z
1
||
z
2
||
z
1
+
z
2
|
2
|
z
1
|
2
+
|
z
2
|
2
+ 2
|
z
1
||
z
2
|
or(
|
z
1
||
z
2
|
)
2
|
z
1
+
z
2
|
2
(
|
z
1
|
+
|
z
2
|
)
2
Taking the square root then proves the triangle inequality. The reason this iscalled the triangle inequality is that, in terms of vectors, we can think of
z
1
,
z
2
and
z
1
+
z
2
as the three sides of a triangle
2
1
z
2
+
z z
1
z
Then the third side (
|
z
1
+
z
2
|
) of a triangle can be no longer than the sum of the lengths of the other two sides (
|
z
1
|
+
|
z
2
|
) nor shorter than the diﬀerence of lengths (
|
z
1
||
z
2
|
).

Finally, for the second inequality, we start by proving that
|
z
+ 1
|
2
=
|
z
|
2
+ 1 + 2
z
= (
|
z
|
2
+ 1
2
z
) + 4
z
=
|
z
1
|
2
+ 4
z >
|
z
1
|
2
for
z >
0. This implies that
|
z
+ 1
|
>
|
z
1
|
for
z >
0. The picture here isthat if
z
is on the right half of the complex plane then it is closer to the point 1than the point
1.
z
1
+
−
z
1
z
z
Given this result, it is simple to see that
|
z
1
|
2
<
|
z
1
||
z
+ 1
|
<
|
z
+ 1
|
2
or, by taking a square root
|
z
1
|
<
|

(
z
1)(
z
+ 1)
|
<
|
z
+ 1
|
which is what we set out to prove.6.1.7 Prove that
a
)
1
n
=0
cos
nx
=sin(
Nx/
2)sin
x/
2cos(
1)
x
2
b
)
1
n
=0
sin
nx
=sin(
Nx/
2)sin
x/
2sin(
1)
x
2We may solve parts
a
) and
b
) simultaneously by taking the complex combination
=
1
n
=0
cos
nx
+
i
1
n
=0
sin
nx
=
1
n
=0
(cos
nx
+
i
sin
nx
) =
1
n
=0
e
inx
The real part of
gives part
a
) and the imaginary part of
gives part
b
). Whenwritten in this fashion, we see that
is a terminating geometric series with ratio
r
=
e
ix
. Thus
=
1
n
=0
r
n
=1
r
1
r
=1
e
Nix
1
e
ix
=
e
12
Nix
(
e
12
Nix
e
12
Nix
)
e
12
ix
(
e
12
ix
e
12
ix
)

We performed the last step in order to ‘balance’ positive and negative exponentialsinside the parentheses. This is so that we may relate both the numerator anddenominator to sin
α
= (
e
e
)
/
2
i
. The result is
=
e
12
(
1)
ix
sin(
Nx/
2)sin
x/
2=
cos
12
(
1)
x
+
i
sin
12
(
1)
x
sin(
Nx/
2)sin
x/
2It should now be apparent that the real and imaginary parts are indeed thesolutions to parts
a
) and
b
).6.2.5 Find the analytic function
w
(
z
) =
u
(
x,y
) +
iv
(
x,y
)
a
) if
u
(
x,y
) =
x
3
3
xy
2
We use the Cauchy-Riemann relations
∂v∂x
=
∂u∂y
= 6
xy
v
= 3
x
2
y
+
(
y
)
∂v∂y
=
∂u∂x
= 3
x
2
3
y
2
v
= 3
x
2
y
y
3
+
D
(
x
)In order for these two expressions to agree, the functions
(
y
) and
D
(
x
) musthave the form
(
y
) =
y
3
+
c
and
D
(
x
) =
c
where
c
is an arbitrary constant. Asa result, we ﬁnd that
v
(
x,y
) = 3
x
2
y
y
3
+
c
, or
w
(
z
) = (
x
3
3
xy
2
) +
i
(3
x
2
y
y
3
) +
ic
=
z
3
+
ic
The constant
c
is unimportant.
b
)
v
(
x,y
) =
e
y
sin
x
As above, we have
∂u∂x
=
∂v∂y
=
e
y
sin
x
u
=
e
y
cos
x
+
(
y
)
∂u∂y
=
∂v∂x
=
e
y
cos
x
u
=
e
y
cos
x
+
D
(
x
)Thus we must have
(
y
) =
D
(
x
) =
c
with
c
a constant. The complex function
w
(
z
) is
w
(
z
) =
c
+
e
y
cos
x
+
ie
y
sin
x
=
c
+
e
y
(cos
x
+
i
sin
x
) =
c
+
e
ix
y
=
c
+
e
iz